IDENTIFIKASI KUAT ACUAN TERHADAP JENIS KAYU YANG DIPERDAGANGKAN DI KOTA KUPANG BERDASARKAN SNI 7973:2013 - Hunggurami, Elia; Utomo, Sudiyo; Messakh, Beddy Y. (Jurnal Teknik Sipil, 2016)
According to results of the test, quality code of each woods is: Timber = E14, Spinach = E14, Red Teak = E12, Candlenut wood = E10 and Cassowary = E15.The compressive strength perpendicular to the wood fibers: Timber= 23,00 MPa, Spinach = 31,00 MPa, Teak Red = 9,67 MPa, Candlenut= 8.67 MPa and cassowary= 21,67 MPa. The compressive strength parallel to the wood fibers: Timber = 70,33 MPa, Spinach = 79,33 MPa, Teak Red = 36,00 MPa, Candlenut= 26,00 MPa and cassowary = 50,00 MPa. Value bending strength of wood: Timber= 132,06 MPa, Spinach= 174,66 MPa, Teak Red= 59,64 MPa, Candlenut= 51,12 MPa and cassowary= 110,76 MPa. The percentage value of compressive strength test comparison between the wood fibers parallel investigation against SNI 7973: 2013: Timber= 164,01%, Spinach= 197.80%, Teak Red= 59.57%, Candlenut= 57.00% and Cassowary= 73,61%. Value percentage ratio of compressive strength test perpendicular to the wood fibers are examined against SNI 7973: 2013: Timber= 365.29%, Spinach= 527,12%, Teak Red= 131,54%, Candlenut= 143,64% and Cassowary= 479,20%. Percentage value comparison test between the flexural strength of the wood studied the SNI 7973: 2013: Timber= 312,64%, Spinach = 445,74%, Teak Red = 121,51%, Candlenut= 154,76% and Cassowary= 215.99%.